Answer:The answer is A
Explanation:
Use the quadratic formula
=
−
±
2
−
4
√
2
x=\frac{-{\color{#e8710a}{b}} \pm \sqrt{{\color{#e8710a}{b}}^{2}-4{\color{#c92786}{a}}{\color{#129eaf}{c}}}}{2{\color{#c92786}{a}}}
x=2a−b±b2−4ac
Once in standard form, identify a, b, and c from the original equation and plug them into the quadratic formula.
5
2
−
7
−
1
8
=
0
5x^{2}-7x-18=0
5x2−7x−18=0
=
5
a={\color{#c92786}{5}}
a=5
=
−
7
b={\color{#e8710a}{-7}}
b=−7
=
−
1
8
c={\color{#129eaf}{-18}}
c=−18
=
−
(
−
7
)
±
(
−
7
)
2
−
4
⋅
5
(
−
1
8
)
√
2
⋅
5
x=\frac{-({\color{#e8710a}{-7}}) \pm \sqrt{({\color{#e8710a}{-7}})^{2}-4 \cdot {\color{#c92786}{5}}({\color{#129eaf}{-18}})}}{2 \cdot {\color{#c92786}{5}}}
x=2⋅5−(−7)±(−7)2−4⋅5(−18)
2
Simplify
3
Separate the equations
4
Solve
Solution
=
7
±
4
0
9
√
1
0